The impact of community and provider-driven social accountability interventions on contraceptive use: findings from a cohort study of new users in Ghana and Tanzania - Petrus S. Steyn; Joanna Paula Cordero; Dela Nai; Donat Shamba; Kamil Fuseini; Sigilbert Mrema; Ndema Habib; My Huong Nguyen; James Kiarie (International Journal for Equity in Health, 2023)
Abstract Background Although contraceptive use has increased over 15 years, discontinuation rates remain high. Contraceptive use is becoming more important when addressing unmet need for family planning. Social accountability, defined here as collective processes for holding duty bearers to account for their actions, is a rights-based participatory process that supports service provision and person-centred care, as well as, informed decision-making among community members regarding their health. A study implemented in Ghana and Tanzania was designed to understand and evaluate how social accountability and participatory processes influences quality of care and client satisfaction and whether this results in increased contraceptive uptake and use. We report here on the relationship between social accountability and the use of modern contraceptives, i.e., contraceptive method discontinuation, contraceptive method switching, and contraceptive discontinuation. Methods As part of Community and Provider driven Social Accountability Intervention (CaPSAI) Project, a cohort of women aged 15 to 49 years who were new users of contraception and accessing family planning and contraceptives services at the study facilities across both intervention and control groups were followed-up over a 12-month period to measure changes contraceptive use. Results In this cohort study over a one-year duration, we did not find a statistically significant difference in Ghana and Tanzania in overall method discontinuation, switching, and contraceptive discontinuation after exposure to a social accountability intervention. In Ghana but not in Tanzania, when stratified by the type of facility (district level vs. health centre), there were significantly less method and contraceptive discontinuation in the district level facility and significantly more method and contraceptive discontinuation in the health centres in the intervention group. In Ghana, the most important reasons reported for stopping a method were fear of side-effects, health concerns and wanting to become pregnant in the control group and fear of side-effects wanting a more effective method and infrequent sex in the intervention group. In Tanzania, the most important reasons reported for stopping a method were fear of side-effects, wanting a more effective method, and method not available in the control group compared to wanting a more effective method, fear of side-effects and health concerns in the intervention group. Conclusions We did not demonstrate a statistically significant impact of a six-month CaPSAI intervention on contraceptives use among new users in Tanzania and Ghana. However, since social accountability have important impacts beyond contraceptive use it is important consider results of the intermediate outcomes, cases of change, and process evaluation to fully understand the impact of this intervention. Trial registration The CaPSAI Project has been registered at Australian New Zealand Clinical Trials Registry (ACTRN12619000378123, 11/03/2019).